(untitled) (Terr@ Plural, 2020)
This paper aims to discuss some conceptions of medium-cities, especially those developed by researchers linked to ReCiMe (Network of Researchers on Medium-Cities). Empirically, we will try to categorize as medium-sized cities Juazeiro (BA) and Petrolina (PE), considering their roles as nodes of the Northeast urban network and at the same time to understand how actions both of State and the capital have been promoting transformations in the urban-regional space of the Sertão do São Francisco.